Implementation of Problem Based Learning Model in 21st Century Learning: Literature Review - Yuliyanah, Yuliyanah; Gumala, Yosi; Yohamintin , Yohamintin (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: determine the improvement of the learning process in the 21st century by applying the problem based learning model learning in elementary school students. Methodology: The learning method used in this scientific work is a literature review or literature review with several stages, namely searching for materials or reference materials on Google Scholar accredited by DOAJ, Sinta, Google Scholar, and so on that are in accordance with the theme to be researched, collecting 30 references that have been obtained. Main Findings: shows that the problem based learning model is effective in improving the quality of learning at various levels of education, including primary and secondary education. Novelty/Originality of this study: This study uses a literature review by analyzing several previous research results and combining them into one so that it becomes a new discovery.